Kulturna raznolikost v zdravstvenih timih - Petrovič, Matic (Obzornik zdravstvene nege, 2025)
Introduction: Cultural diversity in healthcare teams is important for ensuring quality care. Diversity has a positive impact on understanding patients' needs and improving team dynamics. The aim of this study was to examine the presence of different cultures in healthcare teams and healthcare professionals attitudes towards cultural diversity.Methods: We used a qualitative descriptive method. Data were collected through semi-structured interviews, which included demographic data and open-ended questions about health professionals' experiences with cultural diversity in healthcare teams. The purposive sample comprised 28 health professionals from different healthcare disciplines. The interviews were analysed using content analysis.Results: Four main thematic categories were identified: (1) the role of expertise and a professional approach to providing quality care, (2) the importance of effective communication and adaptability, (3) the importance of team dynamics and support in healthcare teams, and (4) cultural diversity and health professionals' perspectives. Most respondents expressed the belief that cultural diversity enriches their experiences and contributes to empathy. Discussion and conclusion: Respondents highlighted both the benefits and drawbacks of cultural diversity. Results show that different skills, experiences and perspectives can be successfully integrated into healthcare teams provided that respectful relationships are established and clearly defined professional guidelines support the quality of care in culturally diverse teams
Keywords: communication; cultural acceptance; ethnicity; etničnost; health professionals; komunikacija; sprejemanje kultur; teamwork; timsko delo; zdravstveni delavci